Dialysis availability for paediatric acute kidney injury in Nigeria - Briggs, Datonye C; Asinobi, Adanze O; Ekpebe, Patrick A; Oshomah-Bello, Oluwatosin E; Oluwatuyi, Korede O; Aliu, Rasaki; Ademola, Adebowale; Ibitoye, Paul K; Akuse, Rosamund M (African Journal of Nephrology, 2024)
Background: Dialysis provides prompt treatment for severe acute kidney injury (AKI) and limits morbidity and mortality. This study compared the current dialysis services for paediatric AKI in Nigeria with earlier studies. Methods: Twenty-four of 34 conveniently sampled paediatric nephrology units across Nigeria responded to an online questionnaire. Results: Responding centres (16, 67%) from the six geopolitical zones were urban tertiary federal/state-owned and mainly in the south. Nineteen centres (79%) offered both peritoneal dialysis (PD) and haemodialysis (HD), 4 (17%) provided HD services only, whereas 1 centre offered PD only. Ten (42%) centres also provided dialysis to neonates. Concerning PD consumables, 75% used improvised PD catheters, with the most common (50%) being nasogastric tubes. In 60% of centres, PD catheter insertion was performed by a paediatrician/paediatric nephrologist; 90% used improvised PD fluids, and all performed PD manually. Concerning HD consumables, 10 (44%) facilities ‘sometimes’ have paediatric dialyzers/bloodlines but mostly these are unavailable for children under five. Challenges with dialysis access include financial constraints, lack of paediatric dialyzers/bloodlines and PD fluids (100%, 75% and 75%, respectively). Compared with earlier studies, current facilities providing dual PD/HD services have significantly (P = 0.021) increased but challenges are unchanged. Conclusion: In Nigeria, dialysis services for paediatric AKI have increased with more facilities providing both HD and PD. Whereas HD is mainly available for older children, acute PD remains predominantly improvised. Continuous kidney replacement therapy is unavailable. There is a need for concerted collaboration between the government and healthcare facilities to ensure consistent availability of age-appropriate dialysis machines/consumables and subsidized paediatric dialysis services.